Acquisition of Email Service Based Android Using NIST - Umar, Rusydi; Riadi, Imam; Muthohirin, Bashor Fauzan (Universitas Muhammadiyah Malang, 2018)
Email is one of the results of the development of information and communication technology. Email is widely used to exchange information by sending and receiving data, such as document files, images, correspondence and others. WithÂ the development of technology and information causing crimes in communicating also growing, the perpetrators of cyber crime commonly referred to as cybercrime. Any crime committed by cybercrime will surely leave the evidence, in this study will make the acquisition of android-based email using the method of national institute of standards and technology (NIST). The results obtainedÂ IPÂ address of the senders email header as digital evidence.